The practicability of activity-based costing in service firms - Haladu, Alhassan (Society of Scientific Research and Education (SSRE), 2016)
The study of Activity-Based Costing (ABC) system is a recent phenomenon in accounting. Modern management requires details of costs and other statistical information which will enable it not only to distinguish efficient departments from inefficient ones and profitable products from unprofitable ones, but to also relate good and bad results to individual managers or those directly responsible for them.The availability of such information in a convenient form enables management to judge the efficiency of past efforts, control current operations, make future plans and above all cut down heavily on its operating costs.ABC is among the latest tools designed to perform such functions.A concept mostly associated with the manufacturing sector, this paper reviews ABC and tests the extent to which it is practicable in service industries. Specifically, the conditions necessary for effective ABC and the reasons for its preferred application was looked into.It is also intended to bring to light the nature and techniques used in its application.To attain this a thorough review was done through conceptual analysis to show the extent to which it is practicable in service firms.It was discovered that ABC can be successfully practice by firms providing services with varying degree of acceptability and positivity.Moreover, its successful application is not only limited to the private sector but includes the public sector as well. This notwithstanding, some service firms shy away from applying ABC while others preferred an alternative system known as activity-based management (ABM).